Optimization of stir–squeeze casting parameters for production of metal matrix composites using a hybrid analytical hierarchy process–Taguchi-Grey approach. Issue 7 (2nd July 2020) - Arunachalam, Ramanathan; Piya, Sujan; Krishnan, Pradeep Kumar; Muraliraja, Rajaraman; Christy, John Victor; Mourad, Abdel-Hamid I.; Al-Maharbi, Majid
ABSTRACT: A hybrid optimization approach using analytical hierarchy process (AHP) combined with Taguchi-Grey has been developed and tested for the first time to optimize the stir–squeeze casting process parameters in the production of aluminium metal matrix composites reinforced with alumina for automotive brake disc application. The AHP method was used for assigning a weight to the response variables, which was based on experts' opinion on the importance of the response variables for brake disc application. For producing brake discs, the optimum process parameters are found to be a squeeze pressure of 100 MPa, squeeze time of 45 s, die preheating temperature of 250°C and stirrer speed of 525 rpm. Also, a confirmatory analysis was carried out to validate these optimum process parameters, and the results indicated enhanced compressive strength of 433 MPa (18.5% increase) and reduced porosity of 5.29% (13.5% decrease) in the composite.